The Making and Circulation of Nordic Models, Ideas and Images - Byrkjeflot, Haldor; Mjøset, Lars; Mordhorst, Mads; Petersen, Klaus (Nordic Studies in a Global Context, 2022)
This critical and empirically based volume examines the multiple existing Nordic models, providing analytically innovative attention to the multitude of circulating ideas, images and experiences referred to as "Nordic". It addresses related paradoxes as well as patterns of circulation, claims about the exceptionality of Nordic models, and the diffusion and impact of Nordic experiences and ideas. Providing original case studies, the book further examines how the Nordic models have been constructed, transformed and circulated in time and in space. It investigates the actors and channels that have been involved in circulating models: journalists and media, bureaucrats and policy-makers, international organizations, national politicians and institutions, scholars, public diplomats and analyses where and why models have travelled. Finally, the book shows that Nordic models, perspectives, or ideas do not always originate in the Nordic region, nor do they always develop as deliberate efforts to promote Nordic interests. This book will be of key interest to Nordic and Scandinavian studies, European studies, and more broadly to history, sociology, political science, marketing, social policy, organizational theory and public management. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.